2013
DOI: 10.1371/journal.pone.0076644
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Enhances Hippocampal Recovery following Binge Ethanol Exposure

Abstract: Binge drinking damages the brain, and although a significant amount of recovery occurs with abstinence, there is a need for effective strategies to maximize neurorestoration. In contrast to binge drinking, exercise promotes brain health, so the present study assessed whether it could counteract ethanol-induced damage by augmenting natural self-repair processes following one or more binge exposures. Adult female rats were exposed to 0 (control), 1 or 2 binges, using an established 4-day model of binge-induced n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 47 publications
6
54
0
1
Order By: Relevance
“…Previous studies have found that non- pharmacological treatments, such as exercise, can reverse both structural and functional deficits related to EtOH exposure (Thomas et al, 2008; Leasure and Nixon, 2010; Maynard and Leasure, 2013; Gallego et al, 2015). Exercise, via the upregulation of neurotrophins, could serve as a protective measure against EtOH’s effects on cognition by re-establishing normal cholinergic/nestin populations, well into adulthood (Gomez-Pinilla and Hillman, 2013; Vivar et al, 2013; Hall et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that non- pharmacological treatments, such as exercise, can reverse both structural and functional deficits related to EtOH exposure (Thomas et al, 2008; Leasure and Nixon, 2010; Maynard and Leasure, 2013; Gallego et al, 2015). Exercise, via the upregulation of neurotrophins, could serve as a protective measure against EtOH’s effects on cognition by re-establishing normal cholinergic/nestin populations, well into adulthood (Gomez-Pinilla and Hillman, 2013; Vivar et al, 2013; Hall et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to wheel running-induced neuroadaptations in ethanol-experienced subjects, concurrent or delayed access to wheel running inhibits ethanol-induced reduction in hippocampal neurogenesis, and expression of hippocampal trophic factors, suggesting a neuroprotective effect (Crews et al, 2004, Maynard and Leasure, 2013, Gallego et al, 2015). This protection could assist with reduction in certain somatic signs of ethanol withdrawal in animals that experienced wheel running during or after ethanol exposure (Leasure and Nixon, 2010, Devaud et al, 2012, McCulley et al, 2012).…”
Section: 0 Discussionmentioning
confidence: 99%
“…Our computational method was evaluated on images from three different laboratories. In this paper, we primarily report results from the data acquired in a previously published study of binge alcohol exposure and voluntary exercise (Maynard and Leasure, 2013). Following intracardial perfusion with saline and 4% paraformaldehyde, brains were removed and post-fixed overnight.…”
Section: Tissue Preparation and Imagingmentioning
confidence: 99%